2023
DOI: 10.1007/s43390-023-00714-w
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of pre-operative SRS scores over time in patients with adolescent idiopathic scoliosis

Abstract: Purpose To determine if preoperative Health Related Quality of Life (HRQoL) has declined in the past two decades for patients with Adolescent Idiopathic Scoliosis (AIS), as measured by the Scoliosis Research Society (SRS) questionnaire. Methods A retrospective review was conducted on AIS patients that underwent surgery at a single institution between 2002 and 2022. Patients were included if they completed an SRS questionnaire preoperatively. A multivariate linear regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Another study of patients with adolescent idiopathic scoliosis and 40-year follow-up after a surgical procedure found that these patients maintained their quality of life over the years 48 . Interestingly, a new study also found that SRS scores of 1,380 adolescents have been steadily declining in the surgical population preoperatively, without any specific reason identified 49 .…”
Section: Spinementioning
confidence: 99%
“…Another study of patients with adolescent idiopathic scoliosis and 40-year follow-up after a surgical procedure found that these patients maintained their quality of life over the years 48 . Interestingly, a new study also found that SRS scores of 1,380 adolescents have been steadily declining in the surgical population preoperatively, without any specific reason identified 49 .…”
Section: Spinementioning
confidence: 99%